Analisis Bibliometrik Perkembangan Penelitian Preservasi Pengetahuan Di Indonesia - Nurhayati, Euis Sri; Salim, Tamara Adriani (IQRA`: Jurnal Perpustakaan dan Informasi, 2023)
This research examines the development of research trends regarding knowledge preservation in Indonesia. The research aims to determine: (1) the development of the number of international publications regarding knowledge preservation in Indonesia in the Scopus database in 2012–2022, (2) the core journal, (3) the contribution of research institutions, (4) researcher productivity, (5) a development map based on subjects or fields, (6) keywords (co-words), and (7) authors (co-authors). Data collection was carried out using the keywords "preservation", "knowledge", and "Indonesia" in "categories, article titles, abstracts, and keywords" in the 2012–2022 time period. The data were analyzed using Microsoft Excel and VosViewer. The research results showed that 467 articles were published in 2012–2022. There are 91 articles (19.49%) published in 2022, and this is the largest number of publications. IOP Conference Series Earth & Environmental Science is a core journal that publishes 39 publications (8.35%). The University of Indonesia is the most contributing institution, and Iskandar, J., is the most prolific writer, publishing six publications (1.28%). Social sciences are the subject or field with the most publications (34.68%). Based on keyword mapping (co-words), there are 9 groups, while based on authors (co-authors), there are 4 clusters. There is also a development trend that is increasing every year.